BRS 331 - Early cycle double-haploid wheat cultivar - Scheeren,Pedro Luiz (2017)
Abstract The wheat cultivar ‘BRS 331’ was developed by Embrapa. It results from an interspecific cross between wheat and maize by double-hapolid method. ‘BRS 331’ shows solid stem in the base of the plant, short leaves and super-early cycle to maturity. It is classified as bread wheat in all of the regions that is recommended in the States of Rio Grande do Sul, Paraná and Santa Catarina, Brazil.